2018
DOI: 10.1016/j.jgeb.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cold pretreatment on shoot regeneration from callus in date palm (Phoenix dactylifera L.) cv. ‘Barhee’

Abstract: Mass propagation of date palm through indirect somatic embryogenesis or organogenesis has attracted the interest of commercial producers. But, this technique still faces some problems that hindered the production of date palm plantlets in vitro. Tissue browning is one of the serious problems that reduce callus growth and shoot regeneration. So the objective of the present study is to investigate the effect of cold pretreatment on callus growth, shoot regeneration, and polyphenol oxidase (PPO) activity during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Browning is one of the problems facing the practical applications of date palm propagation in vitro, and eliminating or minimizing this phenomenon is essential to establishing a successful culture (Al-Mayahi et al, 2020;Al-Mayahi and Ali, 2021). Phenolic compounds production is correlated with the browning intensity of date palm tissues cultures, and many authors proved these findings in their studies (Al-Mayahi et al, 2018;Shehata et al, 2014), however, Mustafa et al (2013) demonstrated that high concentrations of auxins led to accumulating of phenolic compounds and inhibited the growth of cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Browning is one of the problems facing the practical applications of date palm propagation in vitro, and eliminating or minimizing this phenomenon is essential to establishing a successful culture (Al-Mayahi et al, 2020;Al-Mayahi and Ali, 2021). Phenolic compounds production is correlated with the browning intensity of date palm tissues cultures, and many authors proved these findings in their studies (Al-Mayahi et al, 2018;Shehata et al, 2014), however, Mustafa et al (2013) demonstrated that high concentrations of auxins led to accumulating of phenolic compounds and inhibited the growth of cultures.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most significant constraints facing the in vitro tissue of the Date palm is the browning that causes tissue damage a few days after cultivation (Al-Mayahi et al, 2010;Al-Mayahi, 2014). Browning is a significant obstacle to the successful exploitation of these vital trees (Al-Mayahi, 2018 and2019b). Browning of tissues occurs as a result of increased production of TSPCs and their consequent oxidation by the activity of polyphenol oxidase (PPO).…”
Section: Discussionmentioning
confidence: 99%
“…The browning of explants (Figures 1a and 1b) during tissue culture in culture medium is one of the vital constraints for many plant species, especially for woody species. Usually explant browning is affected by emission of phenolic constituents from the cut ends of explants and its callus restriction mechanism was observed by Al-Mayahi et al [22]. This colorization of explants can be controlled by the addition of phenol absorbents, antioxidants and chelating agents into the medium or transferring the explants into fresh culture media at regular times according to several reports [23,24].…”
Section: Prevention Of Browning Problemmentioning
confidence: 99%